Pertumbuhan dan Status Pemanfaatan dari Cakalang (Katsuwonus pelamis) di Perairan Sekitar Manokwari - Ridwan Sala; Tasya Magdalena Br Siahaan; Roni Bawole; Mudjirahayu Mudjirahayu; Mercy Patanda (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Skipjack tuna (Katsuwonus pelamis) has high economic value and opportunities for local and export market demand. The present study aims to investigate growth and exploitation status of the resource. Data collection was carried out in April-August 2021 by collecting catch data from fishermen at four fish landing sites in Manokwari. Skipjack tuna caught from the fishermen were caught in the waters around Manokwari. The size of skipjack tuna measured ranged between 260 mm and 760 mm, with an average monthly size ranging between 540 mm and 595 mm. The relationship between total length and body weight of skipjack tuna followed the equation W = 0.00006L2.7702, where the b value of 2.7702 indicates that the growth pattern of skipjack tuna (K. pelamis) is negative allometric. The growth model using the von Bertalanffy model, found asymptote length (L∞) of 792.75 mm, growth rate (K) of 0.75 year-1 and theoretical age (t0) of -0.0254 years. The total mortality (Z) was 1.32 yr-1. Natural mortality (M) was 0.61 yr-1. The mortality due to capture (F) was 0.71 yr-1. The exploitation rate of 0.54 indicated that the exploitation rate of skipjack tuna in the waters around Manokwari has slightly exceeded the optimum utilization rate. The spawning potential ratio (SPR) value was 16%, which was less than the lower reference point (20%).